Exploring Korean Culture Consumption among Islamic Economics Students in Metro, Lampung, Indonesia: Aligning Behaviors with Al-Ghazali’s Ethics - Marisa, Fina; Sugeng, Anggoro (Universitas Islam Indonesia, 2025)
This study explores the consumption behaviors of fans of Korean culture among the 2020 cohort of Islamic Economics students at IAIN Metro, with a focus on their alignment with Al-Ghazali’s principles of ethical consumption. As global cultural phenomena like the Korean Wave (Hallyu) shape consumer behaviors, this research examines how these influences interact with Islamic ethical frameworks, particularly in prioritizing needs, practicing moderation, and promoting social responsibility. The study aims to provide insights into the ethical dilemmas posed by fan-driven consumerism in a globalized context. Using a qualitative field research approach, data were collected through semi-structured interviews and observations of ten purposively sampled participants. These students, active consumers of Korean cultural products, provided detailed accounts of their spending patterns, motivations, and ethical considerations. The analysis employed thematic coding and triangulation to ensure depth and validity. The findings reveal significant misalignments with Islamic ethical principles. Participants frequently prioritized desires over necessities, exhibited patterns of excessive spending (israf), and showed limited engagement with social responsibilities such as charitable giving. Emotional attachment to fandoms, peer influence, and cultural aspirations were identified as key drivers of these behaviors. While participants demonstrated awareness of Islamic principles, external pressures often outweighed ethical considerations. This study underscores the challenges young Muslims face in balancing global cultural influences with Islamic ethics. It contributes to the discourse on ethical consumption by integrating classical Islamic frameworks with modern consumer dynamics, offering actionable insights for educators and policymakers to promote responsible consumption. Future research should expand the scope to include diverse demographics and explore the role of digital media in shaping consumer behaviors.